Defining `woman': A governmentality analysis of how protective policies are created in elite women's sport - Posbergh, A. (International Review for the Sociology of Sport, 2022)
Women's sport remains a contested realm that frequently features standards and regulations premised on women's inferiority and physiological distinctions from men. In response to these purported sex-based differences, a range of protective policies have been implemented to ostensibly ensure women's safety and health, defend "fair competition" in women's sport, and/or prevent the violation of social and medical boundaries that define who is a "woman." Yet, protective policies encompass a multitude of rationales and strategies, demonstrating the malleability of "protection" in terms of who is protected and why. In this article, I draw from Michel Foucault's theory of "governmentality" to investigate the nuances of protective policies, especially their placed importance on sex differences. To do so, I examine three case studies: World Athletics` (WA) 2019 female eligibility policy, WA's 2019 transgender eligibility policy, and the International Olympic Committee's (IOC) consensus statement on relative energy deficiency in sport (RED-S). Using document texts and semi-structured interviews with eight scientists involved with developing the case studies, I find that protective policies are developed through messy and often contentious processes that selectively draw from varying knowledges and discourses. This then culminates in contrasting methods of defining, protecting, and governing women athletes and their bodies.